Potential Cassava Skin Waste (Manihot esculenta C.) In the Production of Bioethanol by Enzymatic Hydrolysis and Fermentation Using Zymomonas mobilis Bacteria - Permatasari, Nur Umriani; Dali, Seniwati; Wahyuni, Eka Sry (The Journal of Pure and Applied Chemistry Research, 2023)
Cassava is one of the most widely produced agricultural products in Indonesia with cassava peel waste of 20%. Cassava peel contains carbohydrates and stores a high cellulose content so that it has a potential to be a bioethanol. This study aims to utilize cassava peel waste for bioethanol production with an alkaline pretreatment process, cellulase enzyme hydrolysis and fermentation by using Zymomonas mobilis bacteria. Alkaline pretreatment with 14% NaOH is used to hydrolyze lignocellulose. The hydrolysis optimization process enzymatically applies the Surface Response Method (RSM) to determine the optimum conditions at hydrolysis pH in the range of 2-10 and hydrolysis temperature in the range of 30-70 °C by analyzing glucose levels using the Dinitrosalicylic Acid (DNS) method and UV-vis spectrophotometry instruments. Surface Response Method (RSM) is likewise implemented to decide the greatest conditions of the fermentation process. The pH measurement ranges 2-10, and fermentation time takes 6 to 168 hours. Based on the results of research, it results a lignin content of 6.68% (b/b), cellulose content of 58.4% (b/b), and hemicellulose content of 27.3% (b/b). The optimum conditions of the hydrolysis process obtained an optimum glucose level of 9.22mg/mL at pH 2 and a hydrolysis temperature of 50°C. The optimum conditions of the fermentation process use Zymomonas mobilis at pH 6 while fermentation time takes 168 hours analyzed using a refractometer produced a bioethanol content of 37.75% (v/v) and a gas chromatography produced a bioethanol content of 54.94% (v/v).